2012
DOI: 10.4028/www.scientific.net/amr.591-593.507
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of EBW Parameters for 2219 AL-Alloy Using Grey Relation Method

Abstract: Aluminum alloys are the subject of increasing interest in the automotive, as well as aircraft industries. Concerning the assembly, welding was extensively applied in the car industry. Nevertheless, welding defects generated during the process result in reduction in strength of both the weld; and heat affected zone which could limit its applications. Electron beam welding (EBW) has unique advantages over other traditional fusion welding methods due to its high-energy density, deep penetration, large depth-to-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A single-pass weldment of the prepared specimens was conducted using 60 kW Seo TECH-60 electron beam machine at vacuum of 10 −5 mbar. The specimens were welded using the optimal parameters obtained from previous study [13]; these parameters are welding speed 10 mm/s; beam current 18 mA; focus current 909 mA; and sweep size 6. These parameters lead to maximizing hardness, tensile strength, and penetration depth and minimizing bead width.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single-pass weldment of the prepared specimens was conducted using 60 kW Seo TECH-60 electron beam machine at vacuum of 10 −5 mbar. The specimens were welded using the optimal parameters obtained from previous study [13]; these parameters are welding speed 10 mm/s; beam current 18 mA; focus current 909 mA; and sweep size 6. These parameters lead to maximizing hardness, tensile strength, and penetration depth and minimizing bead width.…”
Section: Methodsmentioning
confidence: 99%
“…This work followed an optimization process using Taguchi method with grey relational analysis to find out the optimal weld bead geometry and mechanical properties of 2219 aluminum alloy [13]. Thus, the objective of this study is to clarify the appropriate welding conditions for good welds.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [239] studied the microstructure and mechanical properties of welding joints of components made of 5A06 alloy obtained using double-sided double-arc welding DSAW and laser-TIG LADSW double-sided welding joints. They found that the energy efficiency of LADSW exceeded that of DSAW.…”
Section: The Laser -Mig Hybrid Welding Seems To Be Particularly Usefu...mentioning
confidence: 99%
“…According to [239] Electron beam welding (EBW) is advantageous compared to the other traditional fusion welding methods due to its high-energy density, deep penetration, large depth-towidth ratio and very small HAZ. The authors, using Taguchi method with grey relational analysis, optimized EB welded joint of 2219 alloy, from the yield strength, hardness, and bead geometry.…”
Section: Electron Beam Weldingmentioning
confidence: 99%
“…Oscillation sizes designated as 0, 3, and 6 were utilized. The experiment found the following optimal welding parameters: beam current of 18 mA, focusing current of 909 mA, welding speed of 10 mm/s, and oscillation size of 6 [31]. Extensive research on numerical analysis of fluid transport phenomena and spiking formation of 20 mm thick electron beam welded AA2219 alloy was conducted by Liu et al Beads with partial penetration to base material were fabricated to compare the experimental and numerical simulation results.…”
Section: Introductionmentioning
confidence: 99%